Saharan Dust Events over the Valencian Community (Eastern Iberian Peninsula): Synoptic Circulation Patterns and Contribution to PM10 Levels - Ariadna Huerta-Viso; Javier Crespo; Nuria Galindo; Eduardo Yubero; Jose Francisco Nicolás (Aerosol and Air Quality Research)
Abstract This study assessed Saharan dust events (SDE) passing over the Valencian Community (VC; eastern Spain) during the period of 2014−2017 by investigating the following topics: a) the occurrence of SDE and their impact on PM10 mass concentrations, b) the identification of the favorable synoptic patterns at 850 hPa associated with SDE via cluster analysis and c) the applicability of the gamma probability density function (PDF) in fitting the mass contributions of SDE. We determined that these events affect the VC on ~26% of the days of the year, thereby contributing 3.3 µg m−3 (~23%) to the average PM10 concentration. Five circulation scenarios were identified. In Scenario 1 (17.4%), the transport of Saharan dust was due to the combination of a trough situated over the southwest of the Iberian Peninsula and a high-pressure system centered on western Algeria, Tunisia and eastern Libya. According to the PDF analysis, SDE characterized by this type of pattern were the most likely to substantially increase PM10 mass concentrations. In Scenarios 3 (39.2%) and 5 (19.4%), which contributed to high concentrations of mineral dust in the VC, a high-pressure system was located over North Africa. Scenarios 1, 3 and 5 occurred more frequently during summer, especially Scenario 3 (69%). On the other hand, Scenarios 2 (16.2%) and 4 (7.2%), both characterized by a deep low over the west or northwest of the Iberian Peninsula, typically arose during spring and, to a lesser extent, winter. These two scenarios displayed a lower probability of elevating mineral dust levels in the study area.